2011
DOI: 10.1089/cyber.2010.0374
|View full text |Cite
|
Sign up to set email alerts
|

The Facebook Paths to Happiness: Effects of the Number of Facebook Friends and Self-Presentation on Subjective Well-Being

Abstract: The current study investigates whether and how Facebook increases college-age users' subjective well-being by focusing on the number of Facebook friends and self-presentation strategies (positive vs. honest). A structural equation modeling analysis of cross-sectional survey data of college student Facebook users (N=391) revealed that the number of Facebook friends had a positive association with subjective well-being, but this association was not mediated by perceived social support. Additionally, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
435
7
21

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 725 publications
(524 citation statements)
references
References 36 publications
24
435
7
21
Order By: Relevance
“…This finding is less surprising if we consider it in light of the first main result, which showed that adolescents do not endeavor to further their stereotypical presentation on FB, but rather seek to downplay gender stereotypes. This latter result contradicts findings in other studies to the effect that altered presentation on SNSs is generally associated with lower self-esteem and decreased well-being (Kross et al, 2013); rather is it likely that only a strong misrepresentation has a negative impact, whereas a slight alteration (impression management or "embellishment") of the vision of the self presented online contributes to self-esteem and well-being because of the positive feedback received from Facebook friends ("likes") (Kim & Lee, 2011). A combination of factors could account for these results: a change in gender stereotypes, the trend to describe themselves as androgynous, a progressive "normalization" of Facebook use, and, finally, the educational campaigns for safe and healthy use of Facebook.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This finding is less surprising if we consider it in light of the first main result, which showed that adolescents do not endeavor to further their stereotypical presentation on FB, but rather seek to downplay gender stereotypes. This latter result contradicts findings in other studies to the effect that altered presentation on SNSs is generally associated with lower self-esteem and decreased well-being (Kross et al, 2013); rather is it likely that only a strong misrepresentation has a negative impact, whereas a slight alteration (impression management or "embellishment") of the vision of the self presented online contributes to self-esteem and well-being because of the positive feedback received from Facebook friends ("likes") (Kim & Lee, 2011). A combination of factors could account for these results: a change in gender stereotypes, the trend to describe themselves as androgynous, a progressive "normalization" of Facebook use, and, finally, the educational campaigns for safe and healthy use of Facebook.…”
Section: Discussioncontrasting
confidence: 82%
“…Early studies showed that those adolescents who reported the most frequent selfmisrepresentations in their online profiles also had poorer social skills, lower levels of self-esteem and higher levels of social anxiety and aggression (Harman, Hansen, Cochran, & Lindsey, 2005). More recently, it has been shown that positive self-presentation was found to have an indirect positive effect on subjective well-being through the garnering of perceived social support (Kim & Lee, 2011). Altered self-presentation seems to be less frequent than initially thought, and people tend to present themselves in a rather honest way (Back et al, 2010;Bargh, McKenna, & Fitzsimons, 2002), perhaps because online friends know the user offline and would thus contradict a user's bogus self-presentation by giving negative feedback (Pempek, Yermolayeva, & Calvert, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with findings from Kim and Lee (2011), who explain that the amount of friends an individual has on social media will push them to increase their positive self-presentation. Having a large number of friends on social media is perceived as a form of social affirmation.…”
Section: Fear Of Missing Out Helps Explain Individuals'supporting
confidence: 91%
“…A large number of friends on social media is considered to be a form of social affirmation towards the individual. Individuals tend to strive to keep presenting themselves positively online in order to maintain and add to the number of friends they have on social media (Kim & Lee, 2011). Therefore, Fear of Missing Out can explain the deep and excessive involvement of individuals in all social media activities, including the activity of online self-presentation.…”
Section: Makara Hubs-asiamentioning
confidence: 99%
“…Social networking site users reveal their identity and formulate the impression they wish to produce through presenting desirable information about themselves on their walls as well as within their profiles in social networking sites (Krasnova et al, 2010). Recent empirical study has testified that Facebook users apply various self-presentation 10 strategies (e.g., positive and honest) to disclose information in social networking sites as means to enhance their subject well-being (Kim and Lee, 2011). In addition, Chen and Marcus (2012) claimed that users can select different functionalities of social networking sites to manipulate their self-presentation.…”
Section: Convenience Of Maintaining Existing Relationships Social Netmentioning
confidence: 99%